Nota preliminar sobre la distribución geográfica de Liolaemus wiegmanni (Dum. et Bibr.) (Sauria, Iguanidae) - Cei, José Miguel Alfredo María (1979)
Distribución patterns of Liolaemus wiegmanni in Argentina are analyzed and discusseci. The presence of this species in northern slopes of the Sierras de Córdoba and the Sierra Medina, Tucumán, is reportad. Significant variation in lepidosis points out copulation differences, probably of taxonomic value.